Academic Writing in Malaysia: An Overview - Omar, Asmah Haji (Journal of Modern Languages, 2017)
This study presents the results of a research project to produce a course which provides the consumers with a set of materials for learning/practising writing for academic purposes. The project is envisaged to have results which are pedagogic and academic in nature. The former is used as a package of course materials for practice in academic writing. The second generates further research in academic writing.